2020
DOI: 10.1016/j.celrep.2020.108270
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Receptor-1 and Sympathetic Nervous System Mediate the Beneficial Metabolic Effects of Gastric Bypass

Abstract: SUMMARY The exact mechanisms underlying the metabolic effects of bariatric surgery remain unclear. Here, we demonstrate, using a combination of direct and indirect calorimetry, an increase in total resting metabolic rate (RMR) and specifically anaerobic RMR after Roux-en-Y gastric bypass (RYGB), but not sleeve gastrectomy (SG). We also show an RYGB-specific increase in splanchnic sympathetic nerve activity and “browning” of visceral mesenteric fat. Consequently, selective splanchnic denervation abol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 71 publications
2
41
0
2
Order By: Relevance
“…Another question that remains is to what extent the well established shifts in the intestinal microbiota following RYGB contribute to mesenteric white fat browing. Ye et al (2020) [9] found a splanchnic nerve-mediated decrease in cecal Bacteroidetes in RYGB-operated mice, which is in line with how this bacterial phyla negatively associate with thermogenic markers in subcutaneous white fat of obese patients [27]. It is also possible that splanchnic efferents regulate microbiota residing in mesenteric white fat itself [28] following RYGB, to influence various cellular processes including thermogenesis.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Another question that remains is to what extent the well established shifts in the intestinal microbiota following RYGB contribute to mesenteric white fat browing. Ye et al (2020) [9] found a splanchnic nerve-mediated decrease in cecal Bacteroidetes in RYGB-operated mice, which is in line with how this bacterial phyla negatively associate with thermogenic markers in subcutaneous white fat of obese patients [27]. It is also possible that splanchnic efferents regulate microbiota residing in mesenteric white fat itself [28] following RYGB, to influence various cellular processes including thermogenesis.…”
mentioning
confidence: 82%
“…Next, because the sympathetic nervous system (SNS) is a major driver of thermogenesis [13][14][15], Ye et al (2020) [9] assessed molecular markers of sympathetic tone in jejunal and mesenteric white fat samples such as the rate-limiting enzyme in noradrenaline production tyrosine hydroxylase (TH). Curiously, this revealed higher TH protein levels in human and mouse jejunal mucosa after RYGB where sympathetic nerve terminals do not normally reach.…”
mentioning
confidence: 99%
See 3 more Smart Citations